(untitled) (Journal of Business and Technology (Dhaka), 2017)
The main focus of this study is to analyze the determinants of non-performing loan (NPL) in Non-Bank Financial Institution (NBFI) sector in Bangladesh. Both macroeconomic and firm-specific variables are tested to determine the impact on classified loan ratio. A panel data-set consisting of seven NBFI with a time-span of 12 years (2003-2014) is analyzed for this purpose. Among macroeconomic variables, GDP growth rate, inflation rate and broad money in GDP are used. To capture management ability, firm-specific variables like, loan growth, loan to asset ratio, return on asset and relative size of firm were included in the study. Results show that firm-specific factors were more significant for non-performing loan of the NBFIs. Among macroeconomic variables, money supply was found to have significant impact Journal of Business and Technology (Dhaka) Vol.11(1-2) 2016; 55-67